Chironomid-inferred late-glacial air temperatures at Whitrig Bog, southeast Scotland - Brooks, SJ; Birks, HJB (JOHN WILEY & SONS LTD, 2000)
This paper presents the first chironomid-inferred mean July air temperature reconstruction for the Late-glacial in Britain. The reconstruction suggests that the thermal maximum occurred early in the interstadial, with temperatures reaching about 12 degreesC. There was then a gradual downward trend to about 11 degreesC, punctuated by four distinct cold oscillations of varying intensity. At the beginning of the Younger Dryas, mean July temperatures fell to about 7.5 degreesC but gradually increased to about 9 degreesC before a rapid rise at the onset of the Holocene. The chironomid-inferred temperature curve agrees closely, both in general trends and in detail, with the GRIP ice-core oxygen-isotope curve. The reconstructed temperatures are 2-4 degreesC lower than coleopteran-inferred temperatures but are closer to those inferred from plant macrofossils and glacial equilibrium-line altitudes during the Younger Dryas. Copyright (C) 2000 John Wiley & Sons, Ltd.